Brazilian universities’ approach to plagiarism : the USP case - Ferreira, Marília Mendes (2014)
This  article  examines  the  concepts  of  plagiarism  and  its  approach  by  a prestigious Brazilian university - USP. 42% of its institutes do not provide any  information  about  plagiarism  and  citations  in  academic  papers  in  their websites. They emphasized the citation rules (56.2%) more than the definition of plagiarism (43.8%). Plagiarism was defined as a dishonest act but without guidelines  for  its  prevention  or  punitive  measures. The  article  argues  for  a change of view on the issue: it has to be conceived as a problem of academic writing instruction rather than only as a legal issue.